Effects of clonidine and yohimbine on semicarbazideinduced convulsions and electroconvylsuve shock - YUE Wang; ZHANG Shi-shan (Acta Pharmacologica Sinica, 2016)
Semicarbazide-induced seizures(SCZS) and death were facilitared significantly in adult mice 14 d after intraventricular injection of 6-hydroxydopamine (6-OHDA). Subcutaneous injection of α2-adrenoceptor agonist clonidine (0.1-0.5 mg/kg) reduced SCZS, while α2 –antagonist yohimbine (0.5-5mg/kg) exacerbated SCZS and antagonized the anticonvulsant effects of propranolol. The anticonvulsant activity of clonidine was not abolished following pretreatment with 6-OHDA. These results suggest that the modulation of SCZS by clonidine and yohimbine may be mediated via postsynaptic α2-receptors on central noradrenergic nerve endings. In electroconvulsive shock (ECS), yohimbine exerted anticonvlsant effects, but clonidine did not. In contrast, the anticonvulsant effects of propranolol in ECS were antagonized by clonidine in mice.